Structure and Physical Properties of Polymer Composite Films Doped with Fullerene Nanoparticles. (5th October 2010) - Ahmed, R. M.; El-Bashir, S. M.
Abstract : FullereneC 60 has stimulated intense interest for scientific, industrial, and medical community because of its unique structure and properties. In the present study we prepared fullerene-doped nanocomposite films based on PMMA, PVAc, and PMMA/PVAc blend. Observations made by transmission electron microscope (TEM) showed the uniform dispersion ofC 60 nanoparticles in the polymer matrices. Also, X-ray diffraction measurements indicated thatC 60 has a tendency to form crystallites in the polymer matrices. In addition, the concentration effect of fullereneC 60 was investigated using optical absorption and photoluminescence spectroscopy. The spectroscopic properties of such films recommended their application in photonics and solar energy conversion.